Prokaryotic Responses to Ammonium and Organic Carbon Reveal Alternative CO2 Fixation Pathways and Importance of Alkaline Phosphatase in the Mesopelagic North Atlantic - Baltar, Federico; Lundin, Daniel; Palovaara, Joakim; Lekunberri, Itziar; Reinthaler, Thomas; Herndl, Gerhard J.; Pinhassi, Jarone (Frontiers in Microbiology, 2016)
To decipher the response of mesopelagic prokaryotic communities to input of nutrients, we tracked changes in prokaryotic abundance, extracellular enzymatic activities, heterotrophic production, dark dissolved inorganic carbon (DIC) fixation, community composition (16S rRNA sequencing) and community gene expression (metatranscriptomics) in 3 microcosm experiments with water from the mesopelagic North Atlantic. Responses in 3 different treatments amended with thiosulfate, ammonium or organic matter (i.e. pyruvate plus acetate) were compared to unamended controls. The strongest stimulation was found in the organic matter enrichments, where all measured rates increased >10-fold. Strikingly, in the organic matter treatment, the dark DIC fixation rates —assumed to be related to autotrophic metabolisms— were equally stimulated as all the other heterotrophic-related parameters. This increase in DIC fixation rates was paralleled by an up-regulation of genes involved in DIC assimilation via anaplerotic pathways. Alkaline phosphatase was the metabolic rate most strongly stimulated and its activity seemed to be related to cross-activation by nonpartner histidine kinases, and/or the activation of genes involved in the regulation of elemental balance during catabolic processes. These findings suggest that episodic events such as strong sedimentation of organic matter into the mesopelagic might trigger rapid increases of originally rare members of the prokaryotic community, enhancing heterotrophic and autotrophic carbon uptake rates, ultimately affecting carbon cycling. Our experiments highlight a number of fairly unstudied microbial processes of potential importance in mesopelagic waters that require future attention.